Land Use/Cover Change Analysis Using Remote Sensing Data: A Case Study, Zhengzhou Area, Henan Province, China - Al-Bassam, Bassam F. (Al-Khwarizmi Engineering Journal, 2010)
In the last two decades, arid and semi-arid regions of China suffered rapid changes in the Land Use/Cover Change (LUCC) due to increasing demand on food, resulting from growing population. In the process of this study, we established the land use/cover classification in addition to remote sensing characteristics. This was done by analysis of the dynamics of (LUCC) in Zhengzhou area for the period 1988-2006. Interpretation of a laminar extraction technique was implied in the identification of typical attributes of land use/cover types. A prominent result of the study indicates a gradual development in urbanization giving a gradual reduction in crop field area, due to the progressive economy in Zhengzhou. The results also reflect degradation of land quality inferred from the decline in yield capacity and significant degeneration. Developing land types are Barren land and urban areas (8.02%, and 246.65%). Shrinking land types are water, forest, crop, and grass areas (5.98, 11.52%, 7.09%, and 20.02% respectively). Such changes are the results of physical and anthropogenic factors. The results are expected to provide very useful information for the local government in its future planning.